Blended Learning: Pembelajaran Matematika Bisnis melalui Pemanfaatan Video Animasi - Nicky Dwi Puspaningtyas; Marchamah Ulfa (KALAMATIKA Jurnal Pendidikan Matematika, 2020)
This quantitative study aims to determine the improvement of student learning outcomes in blended learning through the use of animated videos. The study was conducted on 35 students of Universitas Teknokrat Indonesia in the Business Mathematics course. Pretest and posttest are given to subjects to determine learning outcomes before and after treatment. Obtained the average pretest and posttest amounted to 29.4 and 80.4, respectively. Based on the results of Man-Whitney tests, it can be concluded that the mean pretest and posttest scores differ significantly. This means that the use of animated videos in learning Business Mathematics can improve student learning outcomes.